VD_FINDINFO Décision / 2024 / 978 vom 20. Dezember 2024 - VD Tribunal cantonal (2024)
DÉTENTION POUR DES MOTIFS DE SÛRETÉ, RISQUE DE FUITE, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 231 al. 1 CPP (CH), 237 CPP (CH)